PERAN HUKUM ADAT DALAM PENYELESAIAN PERKARA PIDANA PENCEMARAN NAMA BAIK STUDI DI LEMBAGA ADAT LIPU KATOBENGKE - Done, Hardi; Fahri, Heriyadin (Jurnal Ilmu Hukum Kanturuna Wolio, 2025)
This research discusses the role of customary law in the resolution of criminal cases, particularly defamation, in the Lipu Katobengke indigenous community in Southeast Sulawesi. Customary law in this region serves as a mechanism for conflict resolution that emphasizes local wisdom values and social harmony. This study employs a normative-empirical approach, with data collection through interviews, observations, and literature studies. The results of this study indicate that the Lipu Katobengke community still relies on customary leaders to resolve criminal cases, with a mediation process involving all relevant parties. The sanctions applied vary, ranging from light sanctions in the form of fines to heavy sanctions that are now handed over to the authorities. This research emphasizes the importance of preserving the culture and traditions of customary law, as well as the need to enhance the capacity of customary leaders in conflict resolution. Furthermore, cooperation between the indigenous community and the authorities is essential to ensure the sustainability of customary law in a modern context.